SAR Performance of Rectangular Microstrip Antenna for Breast Cancer Hyperthermia Treatment with Different Period of Treatment Procedure - M M, Hassan; Kasumawati, Lias; Norlida, Buniyamin; B S S, Naimullah; Ahmad Tirmizi, Jobli (IOP Publishing, 2021)
Cancer treatment using hyperthermia techniques recently become the interest among researchers in investigating and improving certain deficiencies of the treatment since this treatment has the potential to denaturate cancer into necrotic tissue. Hyperthermia uses high heat from 41℃ to 45℃ at a certain period of time. It is difficult to control the focus position distance of heat distribution on the treated tissue. Therefore, this paper presents the rectangular microstrip as hyperthermia applicator, which deliver the heat on the targeted treated breast cancer tissue with different period of time in order to obtain sufficient heat or SAR distribution. Sim4LifeLight software simulator is used to design, simulate and generate the specific absorption rate (SAR) distribution on the treated tissue. Three frequencies of 434MHz, 915MHz and 2450MHz are used to be compared. Based on the results, 2450MHz shows better performance than the other two frequencies. However, there is a certain limitation, such as skin burn and unwanted hotspots, that need to be further improved. The cancer is sufficiently heating at different operating frequencies at different periods of procedures.